Groundwork for the metaphysics of morals - Kant, Immanuel, 1724-1804 (Rethinking the Western tradition., 2002)
Immanuel Kants Groundwork for the Metaphysics of Morals is one of the most important texts in the history of ethics. In it Kant searches for the supreme principle of morality and argues for a conception of the moral life that has made this work a continuing source of controversy and an object of reinterpretation for over two centuries. This new edition of Kants work provides a fresh translation that is uniquely faithful to the German original and more fully annotated than any previous translation. There are also four essays by well-known scholars that discuss Kants views and the philosophical issues raised by the Groundwork. J.B. Schneewind defends the continuing interest in Kantian ethics by examining its historical relation both to the ethical thought that preceded it and to its influence on the ethical theories that came after it; Marcia Baron sheds light on Kants famous views about moral motivation; and Shelly Kagan and Allen W. Wood advocate contrasting interpretations of Kantian ethics and its practical implications.